1872 Cleveland Gen. Ordinances 102, An Ordinance to Prevent the Careless Use of Fire-Arms, § 2 - (:unkn) unknown (My University, 1872)
That any person who shall discharge, without injury to any other person, any fire-arm while intentionally without malice aimed at or toward any such person, shall be subject to a fine of not less than twenty-five dollars nor more than one hundred dollars, or imprisonment in the work house not exceeding thirty days, or both, at the discretion of the court.
Keywords: DISCHARGE